Psychometric evidence of the Wong-Law Emotional Intelligence Scale (WLEIS) in university students from Lambayeque-Peru - Mendoza Flores, Katy (2024)
Introduction: Emotional intelligence (EI) is a key skill for the personal and academic development of university students. Therefore, it is appropriate to have relevant instruments to measure this construct. Objective: This study aims to analyze the evidence of validity and reliability of the Wong-Law Emotional Intelligence Scale (WLEIS) in university students in the region of Lambayeque, Peru. Method: Our study has an instrumental design. We applied a virtual questionnaire distributed in social networks to 317 university students (124 males and 193 females) from different professional careers, aged between 18 and 30 years (M=20.3; SD=2.7). Confirmatory factor analysis was performed (WLSMV estimator), and internal consistency was assessed. Result: We found four correlated factors, higher order, and bifactor, the first being the one with the best-fit indices: X2(98) = 262.63, p < .001, CFI = .97, TLI = .96, RMSEA = .07 [CI 90%; .06 - .08], SRMR = .04 and WRMR = .91. Internal consistency results using the omega coefficient are ωSEA = .81, ωOEA= .79, ωUOE= .84 and ωROE = .85. Conclusion: The WLEIS in university students in the Lambayeque region of Peru has sufficient evidence of validity and reliability to guarantee the relevance of its application.